Assertive Behavior of School Principals in Creating Excellent School - Moh. Rofiki; Eka Diana; M. Fathul Amin (Universitas Pahlawan Tuanku Tambusai, 2022)
This research was conducted to present the principal's assertive behaviour in creating a superior school. This study uses a qualitative method with a case study approach. The research site is Madrasah Ibtida'iyah Nurul Mun’im Paiton Probolinggo. The results showed that the principal's proactive behaviour in creating an excellent school at Madrasah Ibtida'iyah Nurul Munim Paiton Probolinggo was indicated by the behaviour of providing information; searching for information; giving an opinion; reflecting the message content; giving criticism or praise; accepting criticism or praise; Express feelings; and share feelings. In terms of capabilities, the head of Madrasah Ibtida'iyah Nurul Mun'im Paiton Probolinggo is proven in the form of an attitude of consistency and idealism in deciding and implementing policies; and a person who is honest and open to others so that he becomes a respected and authoritative person. Based on the research, the principal's assertive behaviour can create a superior school through the principal's proactive behaviour, which is romantic, consistent and respectful towards others.